Redescription of Basiria gracilis (Thorne, 1949) Siddiqi, 1963 (Rhabditida, Tylenchidae) from South Africa - Shokoohi, Ebrahim; Abolafia, Joaquín; Mashela, Phatu William (Zootaxa, 2020)
Basiria gracilis is redescribed from North West Province, South Africa, associated with willow (Salix sp.), which is a dominant ornamental tree species in the province. B. gracilis is characterised by its female body length (692–994 µm), lateral field with two longitudinal incisures, weakly cuticularised labial framework, high lip region lacking annuli, stylet 8–13 µm long, axial spermatheca filled with small rounded sperm, conical-elongated female tail with round to pointed terminus (103–146 µm, c=6.1–7.4, c’=8.8–12.1). Morphologically, B. gracilis is closely related to B. paragracilis but the taxa are differentiated on the basis of lip region and stylet morphology. In addition, B. gracilis is reported for the first time from South Africa. Line drawings, LM and SEM illustrations are given for the species.